A Educação Missionária no Brasil: da devoção religiosa ao projeto civilizador da Igreja Presbiteriana dos Estados Unidos (1838-1895) - Zioli, Cláudio Ferraz (2020)
This thesis examines the field of the History of Education, specifically Protestant confessional education, and has been developed based on an analysis of Presbyterian missionary education in the United States and its implementation in Brazil. In this way, the present thesis identifies the concepts of civilization, religion and education present in Presbyterian missionary activities of the 19th century. To do this, it analyzes the Presbyterian Church, the formation of American civilization, the Brazilian historical context during the period of the Presbyterian missions, and the relationships between education and civilization and education and religion present in the official reports of the Presbyterian Church’s Board of Foreign Missions in the United States of America, between the years 1838 to 1895. This time period begins with 1838 because this year marked the formation of a Presbyterian missionary agency for foreign missions and the publication of the first missionary reports. It ends with 1895, corresponds to the last year that the reports presented data considered relevant for this research. This work’s theoretical approach utilizes the concepts of Norbert Elias (1993; 1994a) regarding the civilization process, psychogenesis, sociogenesis, the softening and sophistication of customs, and the analysis of the American civilization process realized by Mennell (2007). To discuss issues relative to religious documents, the theoretical contributions of Michel de Certeau (2014; 2015; 2016a; 2016b; 2017) are used regarding plural culture and production through consumption and the mythic fable. The presence of elements belonging to the American civilization process have been identified, such as conceptions of cleaning, work, economics, cooking, clothing, principles of self-government, self-determination and self-sufficiency, in reports of missions with Native Americans and foreign nations such as India, Liberia, China, Siam, Syria, Mexico, Japan, Korea, Persia, and Laos, as well as various African groups in Brazil. The presence of elements in the American civilization process in the conceptions of religion and education present in the annual reports of the mission boards, demonstrate the existence of a civilizing devotion, or in other words, substituting the ideal of God with the ideal of civilization, manifested and driven by a devotion which oriented the religious, educational and civilizing actions of Presbyterian missionaries in Brazil during the second half of the 19th century.